Environmental Degradation and the Global Ecological Crisis Due to the Fact that the Relationship between Man and the Environment is deteriorating - Al-Jaghifi, Abdul Salam Muhammad Mayel (Al-Adab Journal, 2022)
Humans cause large harm to the atmosphere, water and land by various elements of the environment and to the ecosystem itself. There are a lot of pollution and environmental degradation of man-made, and deliver a comprehensive look at the general scenario, and there are some current trends. Our clima.te at the global and regional level severely contaminated. The protective ozone shield at densely populated latitudes in the Northern Hemisphere is dropping twice as fast as scientists thought a few years ago. Accumulation of greenhouse gases will lead to major changes in weather patterns in the near future, leading to global warming. The destruction of the ozone layer and the further warming of the Earth's surface threaten with catastrophic consequences such as outbreaks of cancerous and tropical diseases, disruption of the ocean food chain, rising sea levels, inundation of many islands, melting of terrestrial small glaciers, floods in many low-lying coastal areas, etc.